Performance Analysis of Universal Filtered Multi-Carrier -Isotropic Orthogonal Transform Algorithm for Next Generation Wireless Networks - R, Dayana.; R, Kumar (International Journal of Engineering and Technology, 2018)
In this paper, a novel time-frequency localization scheme implementation based on isotropic orthogonal transform algorithm (IOTA) prototype filter has been devised for universal-filtered multi-carrier (UFMC) system. UFMC is one of the suggested fifth generation (5G) waveform candidate. Prototype filter IOTA guarantees an optimal localization in the time-frequency domain. By orthogonal a Gaussian pulse in both time and frequency, it finds the name isotropic orthogonal. Due to the characteristics of pulse shaping, IOTA is implemented in UFMC to avoid out-of-band (OOB) radiation and so obtain high spectral efficiency. IOTA-UFMC is compatible for all kind of multiple-input-multiple-output (MIMO) application. This paper evaluate the Â performance of the proposed IOTA-UFMC systems Â through the simulations, the results of 10-4 bit error rate (BER) at low SNR and peak-to-average-power ratio (PAPR) is compared with the existing systems.Â Â Â Â Â